Rescue, Rearing and Training of Elephant Calves at Nandankanan - Kumar, Vinod (Indian Forester, 2002)
Habitats of Elephant (Elephas maximus) need to be protected for survival and sustenance of elephants, a symbol of our natural and cultural heritage. Degradation and fragmentation of habitats of elephants are also result in growing man-animal conflicts. The mighty animal is subjected to unnatural miseries creating problems to animals and abandoned calves. The opportunity however can be a tool of management through rearing and training of such elephants for conservation and management activities. The efforts in captivity at Nandankanan Zoological Park have been narrated here as a possible tool for present and future concerns.